2017
DOI: 10.1021/acs.chemmater.7b00808
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Polyelectrolytes as Water Processable Precursors to Aqueous Compatible Redox Active Polymers for Diverse Applications: Electrochromism, Charge Storage, and Biocompatible Organic Electronics

Abstract: An organic soluble precursor polymer was prepared by direct (hetero)­arylation polymerization of 3,4-ethylenedioxythiophene (EDOT) with a solubilizing, 3,4-propylenedioxythiophene (ProDOT) derivative bearing ester-functionalized side chains. Chemical defunctionalization of the polymer, using base to hydrolyze the esters, yields a conjugated polyelectrolyte (CPE) that is readily soluble in water. This aqueous soluble CPE can then be processed using high-throughput coating methods from water-based inks. Postproc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
78
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 32 publications
1
78
0
Order By: Relevance
“…Developing alternative aqueous‐compatible CPs frequently involves: (i) the incorporation of electron‐rich heterocycles into the polymer backbone that can stabilize positive charge carriers through delocalization, affording materials with redox potentials within the electrochemical window of water, and (ii) functionalization of the polymer backbone with polar groups to assist in the penetration and transport of hydrated electrolyte ions. The latter can be accomplished by targeted postpolymerization modifications that convert hydrophobic, aliphatic side chains required for synthesis and purification with polar groups, such as alcohols and carboxylic acids . Alternatively, the monomer precursor can be functionalized with highly polar side chains, such as oligo(ether), ester, or amide groups, prior to polymerization.…”
mentioning
confidence: 99%
“…Developing alternative aqueous‐compatible CPs frequently involves: (i) the incorporation of electron‐rich heterocycles into the polymer backbone that can stabilize positive charge carriers through delocalization, affording materials with redox potentials within the electrochemical window of water, and (ii) functionalization of the polymer backbone with polar groups to assist in the penetration and transport of hydrated electrolyte ions. The latter can be accomplished by targeted postpolymerization modifications that convert hydrophobic, aliphatic side chains required for synthesis and purification with polar groups, such as alcohols and carboxylic acids . Alternatively, the monomer precursor can be functionalized with highly polar side chains, such as oligo(ether), ester, or amide groups, prior to polymerization.…”
mentioning
confidence: 99%
“…[18,19] Additionally, the broad electroactive response of the high EDOT content polymers in the ProDOT x -EDOT y (P x E y ) series has led to them being effective as capacitive materials for charge storage applications. [20][21][22] In our previous work, we have shown that increasing the EDOT content in the repeat unit of these copolymers lowers the onset of oxidation, increases the capacitance, and lowers the optical gap (E g ) of the resulting material. This trend and the relevant polymer structures are shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…[36] Besides, other highly polar chains e. g. ester and carboxylate salt have also been introduced into ProDOT. [37][38][39] However, few attempts are reported to develop the TT-based structure, though they have been widely employed in organic photovoltaics (OPV), [40] and organic thinfilm transistors (OTFTs). [41] Encouraged by these studies, we herein propose a facile molecular-design strategy to enhance the contrast and switching speed in ECP films ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%